Cape Town central city study, 1972 - Johnston, G; Richardson, B C; Smoor, P (Aeronautical Research Group, 2020)
In March of this year, the third year planning practice class was presented with a project which involved certain studies leading towards the creation of planning proposals for central Cape Town. The class, consisting of five students, was informed that the Cape Town City Council had decided to create a bureau to be known as the Office for Central Planning and Development, O.C.P.D. In order that the O.C.P.D. could make decisions about, and make provision for future development, the class was charged with undertaking research into the present structure which would inform planning proposals to be submitted to the bureau.